THE INFLUENCE OF INFRASTRUCTURE, LABOR AND INVESTMENT ON ECONOMIC GROWTH IN INDONESIA - Hadi Sasana; Ana Hilmiatu Ro’fah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
Economic growth plays a crucial role in the overall well-being of a nation's population. It is composed of various components, each with its own significance in driving economic progress. Among these components are the road infrastructure variable, the labor variable, and the Domestic Investment variable, all of which contribute to stimulating economic growth. Therefore, it is imperative to analyze the extent to which these variables contribute to the economic growth of Indonesia. To conduct this analysis, the Error Correction Model (ECM) is employed as the analytical method. This model enables the determination of both the long-term and short-term effects of the road infrastructure variable, labor variable, and Domestic Investment variable on the Gross Domestic Product (GDP), which serves as an indicator of economic growth. The findings of this study reveal that the road infrastructure variable, labor variable, and Domestic Investment variable have a significant long-term impact on the Gross Domestic Product. Moreover, when considered collectively, these variables exert a substantial influence on the overall GDP. In the short term, although the road infrastructure variable, labor variable, and Domestic Investment variable do not individually exhibit a significant effect on the Gross Domestic Product, their combined impact proves to be significant.